Good practice in occupational health services - The influence of hazardous conditions and nuisance coexisting in the work environment and at home on the course and outcome of pregnancy - Andrzej Marcinkiewicz; Agata Wężyk; Paweł Muszyński; Kinga Polańska; Teresa Makowiec-Dąbrowska; Marta Wiszniewska; Jolanta Walusiak-Skorupa; Wojciech Hanke (Nofer Institute of Occupational Medicine, 2015)
The key activity in good practice of occupational medicine is to control, on a regular basis, the workers' health and how it is affected by the work environment and - consequently - to provide the employers and employees with advice regarding the organization, ergonomics, physiology and psychology of work. Occupational medicine practitioners should remember that certain duties are performed both at work and at home. This issue is particularly important in preventive healthcare of pregnant working women. Taking the above into consideration, we reviewed the literature with respect to nuisance and occupational risk factors, which might be associated with professional and household duties. The research indicates the need to reduce activities that require frequent bending or lifting, put a women at risk of falling or cause excess occupational stress for pregnant women. We would like to draw the doctors' attention to the possibility of exceeding a 4-hour limit of work at video display terminals and negative effects of low physical exercise and sitting for a long time both at work and at home. Since long working hours (over 40 h/week) affect the course of pregnancy negatively, total working time at work (including any additional jobs) and at home must be taken into account in the occupational risk assessment. To sum up, we emphasize that preventive healthcare of pregnant working women should mainly include education programmes. Women need to know how to perform their work safely and pay attention to the scope and frequency of household tasks (duties). Med Pr 2015;66(5):713-724